2019
DOI: 10.1088/1361-6463/ab09be
|View full text |Cite
|
Sign up to set email alerts
|

Functional design of epoxy-based networks: tailoring advanced dielectrics for next-generation energy systems

Abstract: Epoxy resins are widely used as the primary insulation material in many demanding energyrelated applications. As such, the ability specifically to tailor the electrical performance of such systems to meet increasingly demanding insulation situations has considerable utility. This paper describes a new approach to this problem, which is based upon the controlled introduction of specific functional groups into the cured resin's network architecture. Here, two additives are considered, termed functional network m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…As such, we suggest that the molecular structure of the FNM is also important; here, the alkyl chain in GHE contains sixteen carbon atoms while that in GNPE contains only nine. Consequently, additional free volume should be introduced by the GHE, which is consistent with published work on the effect on Tg of GHE [17] and of FNMs with long chain alkyl groups [39]. Secondly, the GNPE contains an aromatic ring within its chemical structure, which may interact physically with the aromatic rings within the backbone of the epoxy network, thereby restricting the mobility of the overall branching moiety.…”
Section: Differential Scanning Calorimetrysupporting
confidence: 74%
See 1 more Smart Citation
“…As such, we suggest that the molecular structure of the FNM is also important; here, the alkyl chain in GHE contains sixteen carbon atoms while that in GNPE contains only nine. Consequently, additional free volume should be introduced by the GHE, which is consistent with published work on the effect on Tg of GHE [17] and of FNMs with long chain alkyl groups [39]. Secondly, the GNPE contains an aromatic ring within its chemical structure, which may interact physically with the aromatic rings within the backbone of the epoxy network, thereby restricting the mobility of the overall branching moiety.…”
Section: Differential Scanning Calorimetrysupporting
confidence: 74%
“…A number of studies have considered such effects with respect to stoichiometric imbalances in anhydride-and amine-cured ERs: while a moderate (~20%) excess of epoxide groups reduces DC conductivity at temperatures below the glass transition temperature (Tg), an excess of amine groups was found to promote conduction [15]; elsewhere, a comparable excess of anhydrides resulted in a pronounced reduction in AC breakdown strength in both the base ER and a nano-filled equivalent [16]. In contrast, an increase in breakdown strength of 10% was seen on incorporating glycidyl 4-nonylphenyl ether into an epoxy network (constant, optimal epoxy/amine stoichiometry) [17], while an increase of twice this magnitude was observed on adding a glycidyl polyhedral oligomeric silsesquioxane into the same base epoxy system (again, constant, optimal epoxy/amine stoichiometry) [18].…”
Section: Introductionmentioning
confidence: 99%
“…The anhydride-hardened systems were cured, initially at 90 °C for 2 h, then at 150 °C for 4 h, as recommended by the manufacturer. Previously, we have reported on the effect of FNMs on thermal stability [17]; the above protocol does not approach the onset of decomposition for any of the systems. The different formulations are hereafter referred to as XTTE or XATTE, where X represents the molar percentage of epoxide groups in the system that was derived from the FNM, A signifies anhydride curing and TTE indicates the appropriate FNM.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that the conductance loss was related to the density of states of special chemical groups, such as aromatic and aliphatic anhydrides. [10][11][12] Similarly, cross-linked networks of epoxy resins can be changed by subtle chemical group differences. 7,11 The length of alkyl chains of epoxy resins was considered to affect the free volume and mobility of cross-linked networks, thus affecting the relaxation polarization loss.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Similarly, cross-linked networks of epoxy resins can be changed by subtle chemical group differences. 7,11 The length of alkyl chains of epoxy resins was considered to affect the free volume and mobility of cross-linked networks, thus affecting the relaxation polarization loss. 7 It was pointed out that the molecular volume of diester segments played an important role in dielectric polarization of anhydride-cured epoxy resins.…”
Section: Introductionmentioning
confidence: 99%